Clinical and biochemical characteristics of patients presenting with pituitary apoplexy - Abbara,A; Clarke,S; Eng,PC; Milburn,J; Devavrata,J; Comninos,A; Ramli,R; Mehta,A; Jones,B; Wernig,F; Nair,R; Mendoza,N; et al. (Endocrine Connections, 2018)
PurposeTo review the clinical and biochemical characteristics and clinical outcome of patients presenting with pituitary apoplexy to a tertiary centre.MethodsWe retrospectively reviewed the clinical features, predisposing factors, biochemistry and clinical outcome of patients presenting with pituitary apoplexy to Imperial College Healthcare NHS Trust between 1991 and 2015.ResultsWe identified 64 patients with pituitary apoplexy (more complete clinical records were available in 52 patients). The median age at presentation was 46.7 years (IQR 31.5–57.0 years). Pituitary apoplexy was the first presentation of pituitary disease in 38/52 of patients and predisposing factors were identified in 28/52. Pituitary apoplexy predominantly occurred in patients with non-functioning pituitary adenomas (47/52). Headache was most commonly described as sudden onset, severe, lateralising to the frontal or temporal regions. Symptoms of meningeal irritation were reported in 7/18 and visual abnormalities in 22/35. A pre-treatment serum cortisol <100 nmol/L was recorded in 12/31 of patients. All patients with visual disturbance had some resolution of their visual symptoms whether managed surgically (14/14) or conservatively (5/5), although pituitary endocrine function did not fully recover in any patient.ConclusionsIn conclusion, these data describe the clinical features of pituitary apoplexy to aid the clinician in diagnosing this rare emergency presentation of pituitary disease. Prospective multicentre studies of the presentation of pituitary apoplexy are required to further characterise presentation and outcomes.